Gross margin and marginal analysis in agriculture of precision and by environments (Costos y Gestión, 2025)
The objective of this work is to reconcile the reports generated by the agricultural economy through the gross margin technique and the marginal analysis model proposed by the costing discipline. Both techniques have a framework with some similarities, but also with semantic and other methodological differences that we propose to consider and point out.  On the other hand, the need to change the current production scheme, which contemplates the fixed application of inputs in a surface unit basis,and then obtain the variable production amount for the batch, is what originates the concept of “environment.”  Taking a specific case and example recently published by an organization of agricultural entrepreneurs and producers, we move forward with the proposal for compatibility that we referred to in the first paragraph, which goes beyond the traditional model of a single result of gross margin per hectare, to present, together with marginal analysis, a report that is able to consider and interpret the so-called “agriculture by environment”.
Keywords: gross margin; marginal analysis; agriculture by environments